Test of Oral Health Literacy in Adults (TOHLA): development and psychometric evaluation of a new scale - Mohtasham GHAFFARI; Sakineh RAKHSHANDEROU; Fábio Luiz MIALHE; Yadollah MEHRABI; Ali SAFARI-MORADABADI (Sociedade Brasileira de Pesquisa Odontológica, 2024)
Abstract This study aimed to develop and rigorously evaluate the Test of Oral Health Literacy in Adults (TOHLA) for the Iranian population, addressing the limitations of existing oral health literacy (OHL) measurement instruments and contributing to the literature on OHL assessment. The development of the TOHLA involved a qualitative approach, which included a comprehensive literature review and semi-structured interviews with a panel of 15 experts from diverse fields and 22 Iranian adults aged 18 to 64 years. The instrument was designed with 48 items categorized into four domains: cognitive skill, communication skill, media skill, and functional skill. Content validity was established through expert input and content validation indices. Construct validity was supported by factor analysis, and concurrent validity was assessed by comparing TOHLA scores with demographic variables. Internal consistency and test-retest reliability analyses were performed to assess the instrument's reliability. The psychometric evaluation of the TOHLA demonstrated strong content validity, construct validity, concurrent validity, internal consistency, and test-retest reliability. The instrument exhibited a high level of internal consistency, with a Cronbach's alpha coefficient of 0.81 for the entire scale. Test-retest reliability was satisfactory, with an intraclass correlation coefficient (ICC) of 0.83. Concurrent validity analysis showed statistically significant associations between OHL scores and demographic variables, supporting the instrument's overall performance. The TOHLA overcomes the weaknesses observed in existing instruments and offers a comprehensive tool with strong psychometric properties to assess the OHL of the Iranian adult population. Researchers, policymakers, and healthcare providers can utilize the TOHLA to address oral health challenges and enhance overall oral health outcomes among Iranian adults.